can someone help me by explaining me how to solve this sum ?
![(a - 3)(a + 2) (a - 3)(a + 2)](https://tex.z-dn.net/?f=%28a+-+3%29%28a+%2B+2%29)
Attachments:
![](https://hi-static.z-dn.net/files/d07/5ea0707c3ab02781c40e34b53146dc2f.jpg)
Answers
Answered by
1
Answer:
DO This
Step-by-step explanation:
(a-3)(a+2)=
=a(a+2)-3(a+2)
=a^2+2a-3a-6
=a^2-a-6
a^2-a-6
Mark Braliest
Similar questions
Math,
2 months ago
Hindi,
2 months ago
Social Sciences,
2 months ago
Math,
4 months ago
English,
4 months ago
Physics,
11 months ago
Social Sciences,
11 months ago